Understanding and elimination of process defects in narrow gap multi-pass fiber laser welding of ferritic steel sheets of 30 mm thickness. Issue 5 (February 2017) - Feng, Jiecai; Guo, Wei; Irvine, Neil; Li, Lin
Abstract Narrow gap (or groove) laser welding involves multiple layer additive manufacture for the joining of thick-section metallic components. Typical defects include porosity, cracking, lack of fusion to sidewalls, and between layers, and component distortion including the closure of the groove. This study aimed to understand the defect formation mechanisms and factors affecting them, and to develop appropriate welding procedures and parameters for joining ferritic steel sheets of 30 mm in thickness. High-quality welded joints in 30-mm-thick Grade 43 ferritic steel sheets have been achieved by multi-pass defocused laser beam welding with filler wire addition. The microstructure and the microhardness of the multi-pass welded joint were found to be affected by the tempering of the subsequent multi-pass welding layers. Post-weld heat treatment on the welded joints were required since, although the strength of the welded joints were higher than that of base metal, the ductility was much lower than that of base metal.